Analisis Praktik Pemasaran Afiliasi Pada Platform E-Commerce Tinjauan Dalam Perspektif Hukum Ekonomi Syariah - Nur Fitriyani; Moh. Mukhsin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Major changes across various sectors, particularly in technology, are driven by the era of the fourth industrial revolution and globalization. The adoption of digital technology in business economic activities has become crucial in this digital era. In Indonesia, the use of digital technology in business has proven its vital role in the local and global economy, as reflected in the increasing number of startups. The shifting consumer behavior, increasingly dependent on the internet, creates new opportunities, such as the rising popularity of Affiliate Marketing. Affiliate marketing, especially on e-commerce platforms like Shopee, provides additional income to content creators and the general public by promoting products. This research focuses on analyzing the application of principles of Islamic economic law in the practice of Affiliate Marketing on Shopee. Through the implementation of Islamic principles, a harmonious cooperation between economic and moral aspects in modern business can be created.